Experimental and analytical study on crack resistance of fully prefabricated steel-UHPC composite deck using PBL connectors. (15th January 2023) - Deng, Kailai; Wang, Kangkang; Liang, Huanwei; Zhao, Canhui; Cui, Bing
Highlights: The crack development, ultimate failure pattern, and load-deflection response of the fully prefabricated bridge deck that use the PBL ribs as anti-cracking structure at the steel–ultra-high-performance concrete (UHPC) interface were experimentally obtained. An analytical model is proposed to describe the cracking mechanism of the fully prefabricated UHPC deck at the steel-UHPC interface; Sensitivity analyses were performed on the main design parameters, and the initial cracking strength of the interface was most sensitive to the height of the PBL connectors. Abstract: To improve the crack resistance of a fully prefabricated composite deck, this study employed perfobond rib (PBL) connectors as the anti-cracking structure at the steel–ultra-high-performance concrete (UHPC) interface. Eight specimens were designed and tested through four-point bending tests. The crack development, ultimate failure pattern, and load-deflection response were observed. According to the test results, the interface employing the PBL connectors achieved satisfactory crack resistance, which was even better close to the cast-on-site reinforced UHPC section. The amount and size of the holes in the PBL connectors, and the placement direction, had an obvious impact on the crack resistance. An analytical model is proposed to describe the cracking mechanism at the steel-UHPC interface. A comparison with the test results revealed that the analytical model has satisfactory accuracy. Sensitivity analyses were performed on the three main design parameters, and the initial cracking strength of the interface was most sensitive to the height of the PBL connectors.